Venture Capital: Business Angels and Covid-19: What Do We Know and Where Are We Going? A Qualitative Literature Review - Lada VEJMELKOVA (Communications of International Proceedings, 2021)
Business angels are hit by an unprecedented coronavirus crisis, like all areas of business. This article aims to evaluate the current knowledge of venture capital investment with the help of business angels in connection with the coronavirus crisis, respectively to identify the typology of individual sources, their content analysis with a particular direct databases and methods of evaluating data. For this purpose, the technique of literary review within the Primo and Web of Science databases and subsequent content analysis of relevant sources were used. The results show that most of the total number of found sources are newspaper articles, then there are scientific peer-reviewed and non-peer-reviewed articles and, last but not least, books. In terms of content, it mainly develops the volume of investments before and after the coronavirus crisis and a description of the change in investor behaviour. The authors use primary and secondary research, data sources such as Crunchbase database, Pitchbook or British Business Bank statistics. These databases are used for statistical data processing. In terms of literature searches and citation analyzes, the Scopus database and the Web of Science are used primarily.
Keywords: venture capital; business angels; covid-19.